Pendidikan Karakter Toleransi Santri Di Pondok Pesantren Al Hasani Kebumen - Wulan, Rizki Nawan; Chamidi, Agus Salim; Wi Hargina, Devi Yaniar (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
AbstractThe purpose of this study is to describe the implementation of tolerance character education for students in Islamic Boarding Schools and the obstacles that arise in the implementation of character education in Islamic Boarding Schools. The study uses a qualitative approach, this research was carried out at the Al Hasani Islamic Boarding School and the subjects of this research were ustadz/ustadzah, boarding school administrators and students. Data collection techniques using observation, interview methods, and documentation methods. Data analysis techniques using data reduction techniques, data presentation and conclusions. Based on the results of the study the following conclusions can be drawn: (1) the implementation of tolerance character education for students in Islamic Boarding Schools use several stages, namely: (a) the organizational; (b) the interpretation stage; (c) the application stage. (2) obstacles to the character education of students are not a few students who do not feel at home, not a few students who are rebellious and difficult to advise, the are students who violate, and it is difficult to handle students who are bit difficult to regulate and behave as they please.Keywords: Character Education, Tolerance and Islamic Boarding School